Pengembangan Media Pembelajaran Permainan Ludo Pada Materi Operasi Pengurangan Kelas 3 MIS Sindangraja: - Agit Darojatil Izzaty; Sunanih; Meiliana Nurfitriani (Universitas PGRI Adi Buana Surabaya, 2021)
This research and development is motivated by the existence of potentials and problems, the potential in this study regarding several learning media that can stimulate or facilitate the learning process. Whereas the problem is that students do not understand the subtraction operation so they have to explain the material repeatedly, this is because there is no stimulus to support the learning process. This can be proven by the average value of 70, and the KKM score in these subjects 75. So it can be concluded that the average score is less than the KKM value. Therefore, a learning media is needed based on these potentials and problems. So that ludo game learning media was created in the MIS Sindangraja class 3 reduction operation. This research is included in the type and design of research development or R&D (Research and Development) of the Borg and Gall type which was carried out at the Sindangraja MIS School with a total of 16 students. The data collection technique was done by using prestest and postest tests. Data were analyzed by SPSS.